2020
DOI: 10.3390/ijerph17020446
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Urbanization and Its Nexus with Eco-Efficiency in China

Abstract: Urbanization has made tremendous contributions to China’s economic development since its economic reforms and opening up. At the same time, population agglomeration has aggravated environmental pollution and posed serious challenges to China’s environment. This article empirically investigates the impacts of China’s urbanization on eco-efficiency, comprehensively reflecting economic growth, resource input, and waste discharge. We first measured the provincial eco-efficiency in China from 2005 to 2015 using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…To reflect interprovincial eco-efficiency in China, this study constructed a composite economicenvironmental-social framework ( Figure 1) that reflects human welfare and sustainability, based on the relevant literature [37,38] as well as OECD ideas about eco-efficiency [39]. The framework also considers the United Nations' "Changing our World: The 2030 Agenda for Sustainable Development" and draws upon Robert Costanza's "full world" model for ecological economy [40].…”
Section: Index System Construction and Data Descriptionmentioning
confidence: 99%
“…To reflect interprovincial eco-efficiency in China, this study constructed a composite economicenvironmental-social framework ( Figure 1) that reflects human welfare and sustainability, based on the relevant literature [37,38] as well as OECD ideas about eco-efficiency [39]. The framework also considers the United Nations' "Changing our World: The 2030 Agenda for Sustainable Development" and draws upon Robert Costanza's "full world" model for ecological economy [40].…”
Section: Index System Construction and Data Descriptionmentioning
confidence: 99%
“…Chen et al found that industrial agglomeration, pollution and ecological efficiency have significant spatial spillover effects, and agglomeration has a significant inverted U relationship with wastewater discharge, sulfur dioxide emission and soot discharge, and a significant U type relationship with ecological efficiency [37]. China's regional ecological efficiency fluctuates, but the overall improvement is noticeable, and the gap between regions is further widened [38]. Ren et al believe that China's overall ecological efficiency is still at a low level, with significant differences between different regions; the eastern ecological efficiency is the highest, followed by the central region, and the gap between the central and western regions is gradually narrowing [39].…”
Section: Introductionmentioning
confidence: 99%
“…There are many extended models of DEA, and the main DEA models widely used to evaluate eco-efficiency include traditional CCR and BCC models [38,39], SBM model with relaxed variables in objective function [40][41][42], DDF model of directional distance function [43,44], and Network DEA model [45][46][47][48]. This study used the Slacks-Based Measure of Efficiency (SBM) model with advantages of being dimension-free and unitvariable [49][50][51] to estimate the efficiency and eco-efficiency in Mongolia. In this study, we took 22 provinces of Mongolia as research space units and estimated the economic efficiency and eco-efficiency of 22 provinces contemporaneous (each year) [52].…”
Section: The Analysis Methods Of Economic Efficiency and Eco-efficiency: Sbm Modelmentioning
confidence: 99%